2010
DOI: 10.3141/2165-03
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Correlation in Multilevel Crash Frequency Models

Abstract: Recent research has shown the importance of spatial correlation in road crash models. Because many different spatial correlation structures are possible, however, this study tested several segment neighboring structures to establish the most promising one to model crash frequency in road networks. A multilevel approach was also used to account for the spatial correlation between road segments of different functional types, which are usually analyzed separately. The study employed a full Bayes hierarchical appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 18 publications
1
47
0
Order By: Relevance
“…Specifically, to gain a more precise estimation of the variability in parameters by considering more complex spatial proximity structures, researchers have proposed a comprehensive investigation of different spatially neighboring structures for both roadsegment-level and area-wide analyses (i.e., Aguero-Valverde and Jovanis, 2010;Wang et al, 2012). As in the study by Dong et al (2014), CPMs accounting for spatial correlation perform better than non-spatial model and also model merely considering 0-1 first order adjacency-based proximity structure.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, to gain a more precise estimation of the variability in parameters by considering more complex spatial proximity structures, researchers have proposed a comprehensive investigation of different spatially neighboring structures for both roadsegment-level and area-wide analyses (i.e., Aguero-Valverde and Jovanis, 2010;Wang et al, 2012). As in the study by Dong et al (2014), CPMs accounting for spatial correlation perform better than non-spatial model and also model merely considering 0-1 first order adjacency-based proximity structure.…”
Section: Introductionmentioning
confidence: 99%
“…Congdon (2006) suggested that ignoring spatial dependence leads to an underestimation of variability. Furthermore, according to Aguero-Valverde and Jovanis (2010), the inclusion of spatially correlated random effects significantly improves the precision of the estimates of the expected collision frequency for road segments. The inclusion of spatial correlation has two main advantages: i) spatial correlation sites estimate the "pool strength" from neighboring sites, thereby improving model parameter estimation (Aguero-Valverde and Jovanis, 2008); and ii) spatial dependence can be a surrogate for unknown and relevant covariates, thereby reflecting unmeasured confounding factors (Cressie, 1993;Dubin, 1988).…”
mentioning
confidence: 98%
“…Proximity structure is a critical element of the CAR prior. While various proximity structures have been investigated [32], the most prevalent structure, 0-1 first-order neighbor, is used to define the proximity matrix in this study. Specifically, if segments and are connected to each other directly, , = 1; otherwise, , = 0.…”
Section: Model Specificationmentioning
confidence: 99%